Modification of Protein-Based Edible Film Characteristics with Different Glycerol Concentrations: A Study on Thickness, Gelation, and Microstructure - Fahrullah, Fahrullah; Basriani, Basriani; Anita, Cis; Febryanti, Farah; Fitri, Fitri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
A thin layer of material added directly to food products that comes from consumable sources is called an edible film. Proteins can be used to create edible films with barrier qualities against oxygen, moisture, and smell, making them appropriate for use as packaging materials that improve product appearance and have preservation effects. Finding out how different glycerol concentrations affect the thickness, gelation duration, and microstructure of protein-based films is the aim of this investigation. A completely randomized design with three treatments and three replications was used in this investigation. The treatments comprised distinct glycerol concentrations, designated as P1 (35%), P2 (40%), and P3 (45%). The protein-based films exhibited thickness values of 0.108–0.113 mm, gelation times of 16.00–20.67 minutes, and a uniform microstructure. At higher concentrations, such as 45%, glycerol resulted in increased porosity and aggregation within the polymer matrix, which in turn led to a reduction in the homogeneity and mechanical strength of the films. A glycerol concentration of 35% proved to be the most effective treatment for the production of a whey-gelatin-based edible film, resulting in a smooth surface and an even distribution of glycerol within the protein matrix. This approach effectively reduced the occurrence of cracks or irregularities.